Pengembangan E-Atlas Keanekaragaman dan Kelimpahan Gastropoda Pantai Sosadale sebagai Media Pembelajaran Zoologi Invertebrata di Rote Ndao - Godlief Pello; Hildegardis Missa; Sardina Ndukang (BEST Journal (Biology Education, Sains and Technology), 2025)
Sosadale Beach is one of the tourist attractions located in Siomeda Village, Rote Tengah District, Rote Ndao Regency, East Nusa Tenggara Province. Sosadale Beach has a fairly wide intertidal zone so that many marine biota live in the zone, one of which is gastropods. Until now there has been no publication regarding the diversity of gastropods in Sosadale Beach. The purpose of this study was to determine the types of gastropods, the level of diversity and abundance of gastropod types in Sosadale Beach and to determine the feasibility of E-Atlas as a learning medium for Invertebrate Zoology courses. The type of research used is research and development. (Research and Development). The research method used in this study is the line transect method, where the drawing of the transect line will be determined based on the substrate. The data obtained were analyzed by identifying and continuing with calculating the diversity and abundance index of gastropods. The results of the data analysis were developed into E-Atlas media using 3 stages of the ADDIE model, namely analysis, design and development. The results showed that the types of gastropods found were 15 species, namely Cypraea annulus, Oliva tremulina, Oliva bulbiformis, Conus figulinis, Bufonaria rana, Conus capitaneus, Haustrum haustorium, Terebralia palustris, Polinices mammilla, Monoplex nicobaricus, Nerita undata, Tritia reticulata, Nerita plicata, Canarium labiatum, and Nassarius stolatus. The results of the diversity index calculation were 2.561119601 with a moderate category and the gastropod abundance index was 7.2 Ind / m2. The results of the E-Atlas validation by media experts obtained a percentage of 86.67% and material experts 96.67% so that an average percentage of 91.67% was obtained with very valid criteria. The conclusion of this study is as follows: gastropods found on Sosadale Beach are 15 species. The gastropod diversity index is 2.561119601 with a moderate category and the gastropod abundance index is 7.2 Ind/m2. The average percentage of validation by media experts and material experts is 91.67%, so the resulting E-Atlas is very valid and suitable for use as a learning medium.